The Influence of Android-Based Multimedia Modules on Static Fluid Material on Understanding The Physics Concepts of High School Students - Winarti Purnama Sari; I Dewa Putu Nyeneng; Ismu Wahyudi (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2019)
Students 'ability to understand the concept of physics is still weak, so it is necessary to use learning resources that are able to improve students' conceptual understanding. This study aims to determine the effect of android-based multimedia modules on understanding the physics concepts of high school students in static fluid material. The sample of this study was students of class XI MIA 1 and XI MIA 2 of SMA 1 Raman Utara. This study was conducted using the type of pretest-posttest control group design. The data obtained were then tested by N-gain analysis, normality test, homogeneity test, independent sample t-test, and effect size test. Data from the study were collected using pretest and posttest with conceptual understanding indicators. The results show that there is an influence of the use of multimedia modules on understanding students' concepts in static fluid material. The results of the study obtained an average N-gain score of the experimental class and control class of 0.54 and 0.31 with the medium category and the effect size value of 2.8 with a large category. The results of different tests using independent sample t-test <0.05 showed that there were significant differences in students' ability to understand concepts using using multimedia-based android modules and students using print modules.